Concentration of Oncogenic Herpesviruses by Methyl Alcohol Precipitation - Goodheart, C. R. (1974)
Oncogenic herpesviruses, like many other viruses, can be concentrated effectively from large volumes of culture fluids by precipitation with methanol with good recovery of infectivity.